(untitled) - Bye, Thomas (New York, 2005)
Complete the activities in the practice book to test and deepen your understanding of the skills and strategies introduced in the student book ,and see for yourself how much you're learning.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy